Issuance of Building Approval (PBG) for Development on Land Affected by Street Plans in Surabaya City - Fatmawati, Ida; Sesung, Rusdianto (PT. Riset Press International, 2024)
This research examines the issuance of Building Approval (PBG) for developments on land affected by road plans in Surabaya City, focusing on the legal consequences and status of such buildings. Employing a normative legal research methodology, the study scrutinizes relevant laws and regulations, including Surabaya Mayor Regulation Number 34 of 2023 and Government Regulation (PP) Number 16 of 2021. The findings reveal that buildings erected on government land without the required IMB or PBG are in violation of these regulations, which may result in their demolition and a lack of legal protection. The study highlights that unauthorized constructions disrupt urban planning and entail legal repercussions under the Job Creation Law, Article 29 Paragraph 1 point c. Buildings lacking IMB and PBG are subject to demolition as they are considered invalid without regional government authorization. The research emphasizes the necessity for rigorous supervision by the Mayor of Surabaya to ensure compliance. Additionally, it explores the broader significance of these permits as essential steps in converting urban spatial policies into operational frameworks, pivotal for road development and urban planning.